Study of the role of parents in the emotional life of their children - Guzmán Huayamave, Kennya (2019)
The present study analyzes the importance of the role of the family as the main socializing agent that should favor the emotional development of the child and ensure a personal and social identity. Therefore, teaching in these spaces is a complex task that generates anxiety for families to achieve the role established by society and above all with the vocation of being parents. The objective of the research study is to determine how the role of parents influences the emotional behavior of 3-year-old children. The methodology used has a mixed approach. At a foundational level, it addresses the theoretical essence of the variables and uses observation and survey techniques. Based on the results, parents should favor the learning of emotional competences since they leave an invaluable mark for their holistic growth.